PKMξ is Essential for Spinal Plasticity Underlying the Maintenance of Persistent Pain. Issue 1 (20th December 2011) - Laferrière, Andre; Pitcher, Mark H; Haldane, Anne; Huang, Yue; Cornea, Virginia; Kumar, Naresh; Sacktor, Todd C; Cervero, Fernando; Coderre, Terence J
Background: Chronic pain occurs when normally protective acute pain becomes pathologically persistent. We examined here whether an isoform of protein kinase C (PKC), PKMξ, that underlies long-term memory storage in various brain regions, also sustains nociceptive plasticity in spinal cord dorsal horn (SCDH) mediating persistent pain. Results: Cutaneous injury or spinal stimulation produced persistent increases of PKMξ, but not other atypical PKCs in SCDH. Inhibiting spinal PKMξ, but not full-length PKCs, reversed plasticity-dependent persistent painful response to hind paw formalin and secondary mechanical hypersensitivity and SCDH neuron sensitization after hind paw capsaicin, without affecting peripheral sensitization-dependent primary heat hypersensitivity after hind paw capsaicin. Inhibiting spinal PKMξ, but not full-length PKCs, also reversed mechanical hypersensitivity in the rat hind paw induced by spinal stimulation with intrathecal dihydroxyphenylglycine. Spinal PKMξ inhibition also alleviated allodynia 3 weeks after ischemic injury in rats with chronic post-ischemia pain (CPIP), at a point when allodynia depends on spinal changes. In contrast, spinal PKMξ inhibition did not affect allodynia in rats with chronic contriction injury (CCI) of the sciatic nerve, or CPIP rats early after ischemic injury, when allodynia depends on ongoing peripheral inputs. Conclusions: These results suggest spinal PKMξ is essential for the maintenance of persistent pain by sustaining spinal nociceptive plasticity.